Adipose-Derived Stem Cells in Tissue Regeneration: A Review. (14th February 2013) - Zuk, Patricia
Abstract : In 2001, researchers at the University of California, Los Angeles, described the isolation of a new population of adult stem cells from liposuctioned adipose tissue. These stem cells, now known as adipose-derived stem cells or ADSCs, have gone on to become one of the most popular adult stem cells populations in the fields of stem cell research and regenerative medicine. As of today, thousands of research and clinical articles have been published using ASCs, describing their possible pluripotency in vitro, their uses in regenerative animal models, and their application to the clinic. This paper outlines the progress made in the ASC field since their initial description in 2001, describing their mesodermal, ectodermal, and endodermal potentials both in vitro and in vivo, their use in mediating inflammation and vascularization during tissue regeneration, and their potential for reprogramming into induced pluripotent cells.